2022
DOI: 10.3389/fcvm.2022.868749
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Causal Effects of Circulating ST2 and Galectin-3 on Heart Failure Risk: A Mendelian Randomization Study

Abstract: BackgroundHeart failure (HF), primarily caused by conditions such as coronary heart disease or cardiomyopathy, is a global health problem with poor prognosis and heavy burden on healthcare systems. As biomarkers of myocardial injury and fibrosis, suppression of tumorigenicity 2 (ST2) and galectin-3 were recommended for prognosis stratification in HF guidelines. However, the causality between these two mediators and HF remains obscure. This study aimed to explore the causal relationship of genetically determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
0
0
Order By: Relevance
“…With the aid of large-scale GWAS datasets, two-sample MR analysis has been widely used to examine the etiological roles of risk factors that reported in conventional observational studies in the development of various cardiovascular diseases (Lamina and Kronenberg, 2021). Similar to our study, previous MR analysis reported non-significant causal associations between cystatin C, galectin-3 and C-reactive protein with HF (van der Laan et al, 2016;Li et al, 2021;Wang et al, 2022), suggesting that these factors may function as bystanders instead of contributors to HF. While most of the previous MR analyses were conducted in European population, our study conducted a separate analysis by utilizing datasets in East Asian to limit the confounding effect of genetic background, which may improve the generalizability of our results.…”
Section: Figuresupporting
confidence: 78%
“…With the aid of large-scale GWAS datasets, two-sample MR analysis has been widely used to examine the etiological roles of risk factors that reported in conventional observational studies in the development of various cardiovascular diseases (Lamina and Kronenberg, 2021). Similar to our study, previous MR analysis reported non-significant causal associations between cystatin C, galectin-3 and C-reactive protein with HF (van der Laan et al, 2016;Li et al, 2021;Wang et al, 2022), suggesting that these factors may function as bystanders instead of contributors to HF. While most of the previous MR analyses were conducted in European population, our study conducted a separate analysis by utilizing datasets in East Asian to limit the confounding effect of genetic background, which may improve the generalizability of our results.…”
Section: Figuresupporting
confidence: 78%
“…For exposures with only one IV, the Wald ratio (WR) method was employed ( Moncla et al, 2022 ). The WR is calculated as the ratio of the effect estimate of the exposure on the outcome to its standard error ( Marouli et al, 2019 ; Wang et al, 2022 ). This method provides a measure of the precision of the estimate and allows for hypothesis testing regarding the causal relationship between exposure and outcome.…”
Section: Methodsmentioning
confidence: 99%